Initial Investigation of Using Planar Interdigital Sensors for Assessment of Quality in Seafood. (5th January 2009) - Syaifudin, A. R. Mohd; Jayasundera, K. P.; Mukhopadhyay, S. C.
Abstract : A planar interdigital sensor-based sensing system has been fabricated for assessment of seafood quality. Our main objective is to sense the molecule of domoic acid presence in mussels. Three peptide derivatives namely sarcosine, proline, and hydroxylproline were used for the initial studies which are structurally closely related to our target molecule. The proline molecule is arguably the most important amino acid in peptide conformation, containing the basic structural similarity to the domoic acid. Three novel interdigital sensors have been designed and fabricated. The initial result shows that sensors respond very well to the chemicals and it is possible to discriminate the different chemicals from the output of the sensor. Results from the analysis have shown that Sensor_1 has better sensitivity compared to other sensors. Sensor_1 was chosen for further analysis with real mussels. The changes in sensor impedance were then analysed with real mussels before and after adding the proline. The presence of proline on the mussel samples was detected by the sensor. Results also showed a good correlation ofR 2 = 0.717 between sensitivity and sample thickness.